DIGITALIZATION OR DIGITAL ECONOMY: PROBLEMS AND PERSPECTIVES - L. Ivanovskaya (Publishing House of the State University of Management, 2019)
The so-called «digitalization» not only as a management tool in economy (digital economy), but also as a historical phenomenon in the evolution of a society and all social life of a human being has been considered. Two different tendencies in the «digitalization» of a social life: one creates real opportunities of historical breakthrough of all mankind to improve its life conditions; the other, dangerous for human being is a possibility of a “cyber slavery”, have been distinguished. Within this context, the tendency of a digital «socialism» and its alternative have been analyzed. It has been noted, that digital economy plays one of the major roles in a struggle for the future. The need to solve certain problems in theoretical and methodological support of digital economy and digitalization as a whole has been shown.